2014
DOI: 10.1002/ppap.201400152
|View full text |Cite
|
Sign up to set email alerts
|

From Killing Bacteria to Destroying Cancer Cells: 20 Years of Plasma Medicine

Abstract: This is an essay that briefly reviews and discusses the application of low temperature plasma (LTP) to kill cancer cells. Some historical background is given and the views and opinions of the author about the present and future of the field are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 27 publications
1
91
0
Order By: Relevance
“…Experimental evidence has shown that LTP does indeed affect cells underneath the tissue surface but what remains unclear is how. One possible explanation is what is referred to as the "bystander effect," which implies that there are chemical signals sent by the cells on the surface (in contact with plasma) to cells in the layer below [41]. These signals would trigger reactions similar to those occurring at the cells on the surface, including the onset of apoptosis.…”
Section: Penetration Of Rons In Tissuesmentioning
confidence: 99%
“…Experimental evidence has shown that LTP does indeed affect cells underneath the tissue surface but what remains unclear is how. One possible explanation is what is referred to as the "bystander effect," which implies that there are chemical signals sent by the cells on the surface (in contact with plasma) to cells in the layer below [41]. These signals would trigger reactions similar to those occurring at the cells on the surface, including the onset of apoptosis.…”
Section: Penetration Of Rons In Tissuesmentioning
confidence: 99%
“…the destruction of biofilms [15] and tumours [16] in the order of 10s of micrometres to millimetres in thickness. APPJ deactivation of biofilms and tumours are often explained by surface cell layers transmitting signals deeper within tissue through cell-to-cell communication [17,18]. Using a synthetic tissue and cell model, we have shown that a He APPJ can directly interact with cells in the sub-surface of tissue (~150 m) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric-pressure plasmas interacting with air and/or water vapor provide a rich source of RONS [62], and could play an important role in oxidation-reduction biology and medicine as previously reviewed [47]. It has been experimentally shown how RONS might intervene in cellular signaling processes to target the destruction of bacteria and or cancerous cells [68][69][70][71][72]. It is now widely accepted that atmospheric-pressure plasmas can be used to deliver RONS into solution or onto a soft medium (e.g., on an agar plate or on living tissue) to regulate cellular functions.…”
Section: Future Directions In the Use Of Microplasma Arrays To Functimentioning
confidence: 99%